Protocol sequence and control co‐design for a collection of networked control systems. (24th February 2015) - Guo, Ge; Wen, Shixi
Summary: This paper is concerned with the simultaneous stabilization of a collection of plants shared by the wireless network with capacity limitation. We use most regular binary sequences (MRBS) to control the medium access status of the plants. The design procedure of the scheduling policy translates to determine two parameters of the MRBS. With the MRBS protocol, each plant is essentially a sampled‐data control system with time varying sampling intervals. We derive a sufficient condition for determining the MRBS protocol that guarantees the controllability, observability, and stability of each plant. Most importantly, we give a methodology for MRBS protocol and controller co‐design, in which the controller has switching gains that are piecewise constant and dependent on the sampling intervals yielded by the MRBS. The main results are established using piecewise Lyapunov functional and the average dwell time technique. It is shown that the method can guarantee simultaneous stabilization of the collection of plants robustly in situations where the controller gain does not match the sampling interval or the sampling interval violates the maximum allowable transmission interval criteria. A numerical example is given to demonstrate the effectiveness of the co‐design method. Copyright © 2015 John Wiley & Sons, Ltd.